The Association of Food Security With Hypertensive Disorders of Pregnancy: A National Health Interview Survey Analysis - Brittany N. Burton; Alexis Sykes; Cecilia Canales; Andrea J. Ibarra; En Chang; Jonathan Dahan; Adam J. Milam; Tina Yu; Catherine Cha (The Journal of Clinical Hypertension)
ABSTRACT Food security is one of the most researched social determinants of health (SDoH), however, there is a lack of literature on the impact of food security on cardiovascular disease in pregnancy. The primary objective was to examine the association between food security with hypertensive disorders of pregnancy. We performed a cross‐sectional analysis of 2019–2022 data from the National Health Interview Survey. The study population included women of childbearing age who were either pregnant or recently pregnant. Logistic regression models were developed to examine the association between food security and hypertensive disorders of pregnancy. Of the 1635 women included in the analysis, the rate of hypertensive disorders  of pregnancy was 11.1% and the rate of low and very low food security was 5.3% and 4.0%, respectively. The prevalence was 5.8% for hyperlipemia, 0.3% for cardiovascular disease, and 10.5% for diabetes mellitus. The odds of hypertensive disorders of pregnancy were statistically significantly increased among women with low food security compared to women with high food security (odds ratio [OR] 2.40, 95% confidence interval [CI]: 1.19–4.81) after adjusting for age, race, ethnicity, insurance status, body mass index, hyperlipidemia, diabetes mellitus, and cardiovascular disease. Further studies are needed to elucidate the causes of hypertensive disorders of pregnancy and interventions to address including the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) and food pantries, as it may be more feasible to address issues of food security among pregnant women.